2022
DOI: 10.1038/s41598-022-05468-5
|View full text |Cite
|
Sign up to set email alerts
|

Attention-guided deep learning for gestational age prediction using fetal brain MRI

Abstract: Magnetic resonance imaging offers unrivaled visualization of the fetal brain, forming the basis for establishing age-specific morphologic milestones. However, gauging age-appropriate neural development remains a difficult task due to the constantly changing appearance of the fetal brain, variable image quality, and frequent motion artifacts. Here we present an end-to-end, attention-guided deep learning model that predicts gestational age with R2 score of 0.945, mean absolute error of 6.7 days, and concordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To validate the superior predictive performance of the proposed PSA-guided dynamic feature fusion CNN (PDFF-CNN) for gestational age prediction, we compared it with existing convolutional neural networks such as ResNet, 45 SE-Net, 46 RepVGG, 47 and EPSANet, 35 along with the methods proposed by Shen et al 21 and Liao et al 19 We chose the methods of the mentioned scholars because Shen's method uses attention mechanisms to enhance the focus on important features, while Liao's method applies deformable convolution to the VGG16 network, both of which are effective in extracting multi-orientation gestational age features. To further demonstrate the effectiveness of PDFF-CNN, ablation experiments were conducted, and the feature extraction process was visualized.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the superior predictive performance of the proposed PSA-guided dynamic feature fusion CNN (PDFF-CNN) for gestational age prediction, we compared it with existing convolutional neural networks such as ResNet, 45 SE-Net, 46 RepVGG, 47 and EPSANet, 35 along with the methods proposed by Shen et al 21 and Liao et al 19 We chose the methods of the mentioned scholars because Shen's method uses attention mechanisms to enhance the focus on important features, while Liao's method applies deformable convolution to the VGG16 network, both of which are effective in extracting multi-orientation gestational age features. To further demonstrate the effectiveness of PDFF-CNN, ablation experiments were conducted, and the feature extraction process was visualized.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…However, most studies have been limited to relatively balanced brain MRI datasets or isolated anatomical regions. 51,52 Recent studies 18,21 reflecting the effectiveness of using fetal brain MRI single-slice strategies as well as multislice or 3D strategies in gestational age prediction have shown that single-slice strategies have higher prediction accuracy than multislice or 3D strategies. Inspired by this, we decided to use only single coronal fetal brain MRI slices in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SFOA is very sensitive to initializing and premature convergence [ 33 ]. Moreover, in MGA, the predictions are made based on single-slice inputs, hypothetically restraining the information available to the network [ 34 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shen et al [ 21 ] used attention-guided, multi-plane ResNet-50 models trained on Stanford data to predict the gestational age. They trained various CNN models based on only imaging features for the prediction of gestational age.…”
Section: Introductionmentioning
confidence: 99%